Analysis of the Music Royalti, Management System, and Royalty Distribution Mechanisms for Songwriter Compensation in Indonesia - Enika Diana Batubara; Porkas Sojuangon Lubis; Yenni Ramadhani Harahap; Daniel Yusuf; T. Elfira Rahmayati; Azulaidin (CV Media Inti Teknologi, 2026)
Background of study: The rapid growth of Indonesia's music industry, driven by digital technology and streaming platforms, has increased the importance of an effective music royalty management system to ensure fair compensation for songwriters. However, various issues remain, including disparities in royalty distribution, lack of transparency in royalty management, and inadequate protection of songwriters' economic rights. These challenges may hinder the sustainability of the music industry and reduce the welfare of songwriters. Aims and scope of paper: This study aims to analyze the influence of the music royalty management system and royalty distribution mechanisms on songwriter compensation in Indonesia. The study focuses on evaluating the effectiveness of royalty management practices and their contribution to protecting the economic rights of songwriters. Methods: This study employed a quantitative research method with a descriptive approach. Data were collected through questionnaires distributed to songwriters, independent musicians, music industry practitioners, and stakeholders who understand the music royalty system in Indonesia. Purposive sampling was used to select 30 respondents. The data were analyzed using multiple linear regression analysis. Result: The findings indicate that the royalty distribution mechanism has a significant positive effect on songwriter compensation, with a significance value of 0.000 (<0.05) and a t-value of 12.411 (>2.048). Simultaneously, the royalty management system and royalty distribution mechanism significantly influence songwriter compensation, as indicated by an F-value of 106.356 (>3.35). Furthermore, the coefficient of determination (R²) value of 0.887 indicates that 88.7% of songwriter compensation is explained by these two variables. Conclusion: The study concludes that transparent and effective royalty management and distribution mechanisms play a crucial role in improving songwriter compensation in Indonesia. Strengthening accountability, transparency, and digital royalty management systems is essential to ensure fair economic protection and support the sustainable development of the Indonesian music industry.